Energy : - Demirel, Yaşar (Green energy and technology, 2012)
"Understanding the sustainable use of energy in various processes is an integral part of engineering and scientific studies, which rely on a sound knowledge of energy systems. Whilst many institutions now offer degrees in energy-related programs, a comprehensive textbook, which introduces and explains sustainable energy systems and can be used across engineering and scientific fields, has been lacking. Energy: Production, Conversion, Storage, Conservation, and Coupling provides the reader with a practical understanding of these five main topic areas of energy including 130 examples and over 600 practice problems."--From publisher description.